Tape, tape cartridge, and magnetic recording and reproducing device - IMAI TAKASHI; FUKUOKA YUKI; SAWAI DAISUKE; MATSUI TAKASHI (2023)
The present invention provides a magnetic layer having a non-magnetic support and a ferromagnetic powder, the magnetic layer being characterized in that: in a small-angle X-ray scattering spectrum of the non-magnetic support as determined by small-angle X-ray scattering measurement, the q value of the magnetic layer is greater than the q value; the ratio (Imax/Imin) of the scattering intensity Imax at the q value qmax at the maximum value of the scattering intensity change rate to the scattering intensity Imin at the q value qmin at the minimum value of the scattering intensity change rate is 2.7 or more, qmin < qmax, and the glass transition temperature (Tg) of the non-magnetic support is 140 DEG C or more. 本发明提供一种具有非磁性支撑体和含有强磁性粉末的磁性层，在通过小角度X射线散射测定而得的上述非磁性支撑体的小角度X射线散射光谱中，在q值为的区域内，散射强度变化率的极大值下的q值qmax处的散射强度Imax与散射强度变化率的极小值下的q值qmin处的散射强度Imin之比I max/Imin为2.7以上，qmin＜qmax，并且上述非磁性支撑体的玻璃化转变温度Tg为140℃以上的磁带、包括上述磁带的磁带盒及磁记录再现装置。